Telomere Length Variations in Aging and Age-Related Diseases - Rizvi, Saliha; Raza, Syed Tasleem; Mahdi, Farzana (Current Aging Science, 2014)
Telomeres are gene sequences present at chromosomal ends and are responsible for maintaining genome integrity. Telomere length is maximum at birth and decreases progressively with advancing age and thus is considered as a biomarker of chronological aging. This age associated decrease in the length of telomere is linked to various ageing associated diseases like diabetes, hypertension, Alzheimer’s disease, cancer etc. and their associated complications. Telomere length is a result of combined effect of oxidative stress, inflammation and repeated cell replication on it, and thus forming an association between telomere length and chronological aging and related diseases. Thus, decrease in telomere length was found to be important in determining both, the variations in longevity and age-related diseases in an individual. Ongoing and progressive research in the field of telomere length dynamics has proved that aging and age-related diseases apart from having a synergistic effect on telomere length were also found to effect telomere length independently also. Here a short description about telomere length variations and its association with human aging and age-related diseases is reviewed.
Keywords: Aging